IDENTIFIKASI MORFOLOGI SPERMA KATAK FAMILI (BUFONIDAE) MENGGUNAKAN METODE GALLI MAININI: KARAKTERISTIK MORFOLOGI SPERMATOZOA KATAK FAMILI BUFONIDAE - Ardiyansyah, Fuad; Endah Tri Kusumawati, Dini; Prasetyo, Joko; Rafidha Kasyim, Ria; As'ari, Hasyim (Program Studi Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2024)
Frogs and toads belong to the same order, Anura, but toads usually have rough and bumpy skin like those in the Bufonidae family. This study aims to study the morphological characteristics of male frog sperm cells using the galli mainini method, using pregnant women's urine containing the hormone human Chorionic Gonadotropin (hCG) to stimulate sperm production. Urine is injected into the frog's abdominal membrane, and after 30 minutes, the frog is stimulated to excrete urine containing sperm. The results showed that the length of Bufonidae frog spermatozoa ranged from 32.54 μm to 73.31 μm with an average of 56.35 μm. The acrosome and tail of the spermatozoa are almost the same length, making these two parts difficult to distinguish. In conclusion, optimization of the dose and concentration of the hCG hormone is needed for further research and exploration of its long-term effects on male frogs.